Genus Trichocera in Morocco: first records from Africa and a new species (Diptera: Trichoceridae) - Driauach, Ouafaa; Krzemińska, Ewa; Belqat, Boutaïna (Zootaxa, 2015)
Till now only two species of the genus Trichocera, T. annulata and T. hiemalis, were recorded from north Africa. Herewith, we document seven species from Morocco, which extend distribution of the genus and the family to most southern localities of the western Palearctics in Africa (mountain ranges: the Rif, Middle Atlas and Beni Snassen). The following species were found: one new species in the nominate subgenus Trichocera (Trichocera) marocana, n. sp., and six of the subgenus Trichocera (Saltrichocera) (saltator, sardiniensis, pappi, annulata, regelationis, rufescens). The remarkably high share of the regelationis group of species in this southern fauna is discussed in view of tolerance of these species to warm climate.